State Authority and The Regulation of Maritime Fencing Practices in Indonesia - Ida Kurnia; Luo Yuan Yuan (International Law Discourse in Southeast Asia, 2026)
The sea plays a strategic role in supporting the social, economic, environmental, and defense life of a country, especially for Indonesia as an archipelagic nation. Based on UNCLOS 1982 and national regulations, Indonesia has sovereignty over its maritime territory to regulate, manage, and utilize it. However, the practice of fencing maritime areas by individuals, groups, corporations, and foreign parties often violates the law and causes various problems, such as restricting access for traditional fishermen, ecosystem damage, and social conflict. This fencing action is often carried out without official permission or is contrary to marine spatial planning, and opens up opportunities for resource exploitation by foreign parties. This paper aims to analyze the state's authority to enforce the law against the practice of fencing maritime areas, using a normative approach through a review of laws and legal principles. The focus of the study includes the limits of state authority at sea, forms of fencing violations, and legal steps that can be taken to enforce the rules. It was found that although the state has a strong legal basis, implementation in the field still faces obstacles in inter-institutional coordination, overlapping authorities, and the absence of specific regulations related to restrictions on the use of marine space by the private sector. This paper recommends strengthening regulations, increasing monitoring capacity, and involving coastal communities in decision-making to realize marine management that is fair, sustainable, and in line with the principle of state sovereignty